The Influence of Government Expenditure in Education and Health Sector on The Poverty in Gorontalo - Windiyawati M Niuwa; Fahrudin Zain Olilingo; Ivan Rahmat Santoso (Jambura Equilibrium Journal, 2019)
This study aims to determine how much influence the Government Expenditure of Education Sector and Health Sector on Poverty in Gorontalo City. This research uses quantitative methods. The data used in this study are secondary data sourced from the Central Statistics Agency and the Directorate General of Fiscal Balance Ministry of Finance using the econometrics method through multiple linear regression equations in the form of 10-year time series data (2008-2017). The results showed that 1) Education sector government expenditure has a positive effect on the level of poverty in Gorontalo City 2) Government health sector expenditure has a negative effect on poverty levels in Gorontalo City. Keywords: Poverty, Government Expenditure, Education Sector, Health Sector.